2022
DOI: 10.15252/embj.2021108918
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional locus controls motor neuron differentiation through short and long noncoding RNAs

Abstract: The transition from dividing progenitors to postmitotic motor neurons (MNs) is orchestrated by a series of events, which are mainly studied at the transcriptional level by analyzing the activity of specific programming transcription factors. Here, we identify a posttranscriptional role of a MN-specific transcriptional unit (MN2) harboring a lncRNA (lncMN2-203) and two miRNAs (miR-325-3p and miR-384-5p) in this transition. Through the use of in vitro mESC differentiation and single-cell sequencing of CRISPR/Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…As an example, we tested the performance of the new set-up on lncMN2-203, whose isolation from 1 mg of DSS-treated extracts was found enhanced. Moreover, we found that the DSS treatment also improved the recovery of miR-466i-5p, previously identified as a functional lncMN2-203 partner (Carvelli et al, 2022). In line with the binding specificity, only background enrichments were found for miR-669a-5p and miR-325-3p, previously shown as non-interacting miRNAs.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…As an example, we tested the performance of the new set-up on lncMN2-203, whose isolation from 1 mg of DSS-treated extracts was found enhanced. Moreover, we found that the DSS treatment also improved the recovery of miR-466i-5p, previously identified as a functional lncMN2-203 partner (Carvelli et al, 2022). In line with the binding specificity, only background enrichments were found for miR-669a-5p and miR-325-3p, previously shown as non-interacting miRNAs.…”
Section: Discussionsupporting
confidence: 64%
“…In this setting, we also checked for miRNAs known to co-precipitate with lncMN2-203 and we confirmed that miR-466i-5p was significantly enriched in the MN2 as compared to the U1 PD (Figure 1C, left panel). MiR-669a-5p and miR-325-3p, used as negative controls, were almost undetectable in both the conditions (Figure 1C, middle and right panels), in line with their known inability to interact with the lncRNA (Carvelli et al, 2022).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations